Stimuli-Responsive Biomass Cellulose Particles Being Able to Reversibly Self-Assemble at Fluid Interface - Zhu, Yue; Chen, Tingting; Cui, Zhenggang; Dai, Hong; Cai, Li (Frontiers in Chemistry, 2020)
Stimuli-responsive surface-active microcrystalline cellulose(MCC) particles are obtained by interaction with a conventional cationic surfactant cetyltrimethylammonium bromide (CTAB) in aqueous media, where MCC are in situ hydrophobized by adsorption of CTAB molecules in water via electrostatic interaction, and with the in situ hydrophobization removed by adding an equimolar amount of an anionic surfactant sodium dodecyl sulfate (SDS), which prefer to form ion pairs with CTAB and thus making them desorb from surface of MCC. The trigger is the stronger electrostatic interaction between the oppositely charged ionic surfactants than that between the cationic surfactant and the negative charges on particle surfaces. Reversible O/W Pickering emulsions can then be obtained by using the MCC in combination with trace amount of CTAB and SDS. With excellent biocompatibility, biodegradability, renewability, as well as low toxicity, the biomass cellulose particles which can be made stimuli-responsive and able to reversibly self-assemble at fluid interface, become ideal biocompatible particulate materials with extensive applications involving emulsions and foams.